THE EFFICACY OF FLAVONOID IN RED MULBERRY ON REDUCING FREE RADICALS AND ALVEOLAR MACROPHAGES DUE TO CIGARETTE SMOKE EXPOSURE IN WISTAR RATS - Rivan Virlando Suryadinata; Dita Sukmaya Prawitasari; Indira Pradita Rochim (Media Gizi Mikro Indonesia, 2021)
Background. Free radicals in cigarette smoke will hurt health when they enter to the respiratory tract. An excessive increase of free radicals in the body will cause oxidative stress. Free radicals are generated physiologically by the body's metabolism and can neutralize antioxidants in the body. An imbalance number of free radicals will result in cell damage and death. It has characterized by an increase in malondialdehyde levels in the blood and alveolar macrophages in the lung tissue. Giving red mulberry (Morus rubra) as an intake of antioxidants from outside the body can prevent adverse effects of cigarette smoke. Objective. This study analyses flavonoids' impact on red mulberry in reducing free radicals due to exposure to cigarette smoke by lowering levels of malondialdehyde and alveolar macrophages. Method. This research is experimental with a post-test control group design using male Wistar rats (Rattus novergicus) as experimental animals. Treatment of experimental animals through red mulberry per oral and exposure to cigarette smoke had conducted for 30 days. The parameters used were levels of malondialdehyde and alveolar macrophages in the lung tissue. Results. The research showed an increase in free radicals in the group exposed to cigarette smoke. Increasing intake of red mulberry can further reduce malondialdehyde levels and the number of alveolar macrophages (p<0.05). Conclusions. The antioxidants in red mulberry can reduce malondialdehyde levels in the blood and the number of alveolar macrophages in lung tissue due to exposure to cigarette smoke.